2013
DOI: 10.3201/eid1912.130284
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Cysticercosis Caused by LarvalTaenia crassicepsTapeworm in Immunocompetent Woman, Germany

Abstract: Human cysticercosis caused by Taenia crassiceps tapeworm larvae involves the muscles and subcutis mostly in immunocompromised patients and the eye in immunocompetent persons. We report a successfully treated cerebellar infection in an immunocompetent woman. We developed serologic tests, and the parasite was identified by histologic examination and 12s rDNA PCR and sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 12 publications
1
48
0
2
Order By: Relevance
“…Humans can get infected with the parasite after the accidental ingestion of viable ova shed in canid faeces. Cysticerci are usually located in the subcutis, muscles, eyes and, rarely, the central nervous system (Lescano & Zunt 2013;Ntoukas et al 2013). In the present study we identified T. crassiceps in 10 out of 57 foxes (prevalence 17.5%; Table I), all of which were living in lowlands.…”
Section: Resultsmentioning
confidence: 54%
“…Humans can get infected with the parasite after the accidental ingestion of viable ova shed in canid faeces. Cysticerci are usually located in the subcutis, muscles, eyes and, rarely, the central nervous system (Lescano & Zunt 2013;Ntoukas et al 2013). In the present study we identified T. crassiceps in 10 out of 57 foxes (prevalence 17.5%; Table I), all of which were living in lowlands.…”
Section: Resultsmentioning
confidence: 54%
“…In the recent years, several human infections with the larval stage of the tapeworm Taenia crassiceps have emerged, 1 most often in immunosuppressed individuals. [2][3][4][5][6][7] The tapeworm is maintained in a sylvatic cycle involving foxes as natural final hosts and rodents as intermediate hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Among animals, fatal cases of T. crassiceps cysticercosis were described in, e.g., a ring-tailed lemur (Lemur catta) from Madrid Zoo in Spain (Luzon et al 2010), in a chinchilla (Chinchilla laniger) from Switzerland (Basso et al 2014), in a wild red fox (Vulpes vulpes) in Croatia (Konjevic et al 2016) and the subcutaneous form doi: 10.17221/82/2017-VETMED in a dog in Germany (Nolte et al 2016). As for recent human infections, e.g., two cases in immunocompetent patients in Germany were described (Ntoukas et al 2013;Roesel et al 2014); further, cysticercosis was described in a HIV-positive woman from Switzerland who worked as an employee in a zoo (Anikpeh et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In human populations, the most vulnerable individuals are HIV-positive and immunocompromised patients (Arocker-Mettinger et al 1992;Francois et al 1998). Metacestodes of T. crassiceps have rarely been diagnosed in immunocompetent patients (Ntoukas et al 2013).…”
mentioning
confidence: 99%